THE CULTURAL SPECIFICITY OF AMERICAN IDIOMS (Web of Teachers: Inderscience Research, 2025)
This article delves into the cultural specificity of American idioms, exploring the intricate connections between language, culture, and history in American English. It examines how idiomatic expressions reflect various aspects of American society, including the influence of indigenous peoples, immigrants, African American Vernacular English (AAVE), and popular culture. The article also investigates how idioms evolve in response to societal changes, including the digital age and technological advancements. Additionally, it addresses the challenges in translating American idioms, considering their reliance on cultural context. Ultimately, the article highlights the importance of studying idioms to understand the broader intersection of language, culture, and identity in the United States.